Improving The Students’ Ability In Writing Recount Text Through Guided Picture of Class X DKV 2 Semester 1 at SMKN 1 Banyuwangi In The 2017/2018 Academic Year - Karyati, Karyati (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2018)
This classroom action research discussed certai ways to solve studentsdifficulties in composing recount, and the researcher would like to developthe technique of learning composing recount through guided picture, andthe problem of this research is: How can the students’ ability in writing recounttext through guided picture of X DKV 2 Semester 1 at SMKN 1 Banyuwangi inthe 2017/2018 Academic Year be improved?. This classroom action researchapplied the strategy in order to improve the students’ ability in writingcomposition of recount text, and the strategy which is used in teachingwriting composition is the use of guided picture as the media.. The use of guided pictures as media in teaching writing composition ofrecount can improve the students’ ability of class X DKV 2 SMKN 1Banyuwangi. It can be seen in the result of cycle I and cycle II. Frompreliminary test, the students writing composition of recount score rangedfrom 55 to 68, there were 24 students. It gradually improved to 37.1%, it meansthat the score range in cycle 1 was from 55 to 68 there were 11 students. Incycle 2, there were 9 students in the score range from 55 to 68. It means thatthere was 5.7% achievement. It can be concluded that the test result frompre-action, cycle 1, to cycle 2 have had improved significantly based on thecriteria of success which has been stated in previous chapter that is 75%. On the other hand, it can be concluded that the students’ motivation andinterest in learning writing composition of recount are also improved